2023
DOI: 10.1002/aenm.202300413
|View full text |Cite
|
Sign up to set email alerts
|

Co‐MOF as Stress‐Buffered Architecture: An Engineering for Improving the Performance of NiS/SnO2 Heterojunction in Lithium Storage

Abstract: Heterostructures with interfacial effects have exhibited great potential for improving the electrochemical kinetics of electrode materials. However, the application of heterostructures is hampered by complicated synthesis parameters and numerous single components. Herein, a multiple‐templating synthesis strategy is proposed to improve the interfacial effect of heterojunction composites, mitigate volume variation upon lithiation/de‐lithiation, and increase interfacial compatibility with poly‐oxyethylene‐based (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Moreover, when the current density was restored to 0.1 A g −1 , the capacity of NiO/SnO 2 @NG still recovered to 789.1 mA g −1 , which indicated that the heterojunction composite had excellent ion transport capacity and effective active sites. 26 Meanwhile, the charge–discharge distributions of NiO/SnO 2 @NG at different current densities are given in Fig. 4(c) indicating little polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, when the current density was restored to 0.1 A g −1 , the capacity of NiO/SnO 2 @NG still recovered to 789.1 mA g −1 , which indicated that the heterojunction composite had excellent ion transport capacity and effective active sites. 26 Meanwhile, the charge–discharge distributions of NiO/SnO 2 @NG at different current densities are given in Fig. 4(c) indicating little polarization.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the introduction of Biotite as nucleation sites weakens the induced surface phenomenon process on the electrode/electrolyte interfaces. Further, we measured both the capacitive contribution at different scan rates using the following equation i ( V ) = k 1 v + k 2 v 0.5 The i ( V ), k 1 v , and k 2 v 0.5 are the total current, surface-induced capacitive controlled current, and diffusion-controlled current, respectively. Figure c indicates that by increasing the scan rate, the surface-controlled charge also increases.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This suggests that the introduction of Biotite as nucleation sites weakens the induced surface phenomenon process on the electrode/electrolyte interfaces. Further, we measured both the capacitive contribution at different scan rates using the following equation 47 i…”
Section: Electrochemical Characterization 321 Electrochemical Charact...mentioning
confidence: 99%
“…7a shows the shape of curves with the same trend as the potential increases and polarization decreases during cathodic and anodic processes. 3 The charge storage mechanism is derived from the following equation: i = av b where the value of i is the peak current at the time of measurement, v denotes the scan rate, and b is an indicator of the type of charge storage mechanism, which can be obtained from log( i )–log( v ). 32,33 If b = 1 it indicates a pseudocapacitor-controlled charge storage process and b = 0.5 indicates an ion diffusion-controlled charge storage process.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 However, commercial graphite cannot satisfy the excellent electrochemical activity and electrical conductivity of anode materials because of drawbacks such as low theoretical capacity (372 mA h g −1 ) and low safety (lithium precipitation). 3 Currently, various metals and metal oxides/sulfides are promising anode materials for LIBs considering their high capacity, great conductivity and low potential. Nevertheless, low conductivity and volume expansion severely limit their multiplicative performance and cycling stability.…”
Section: Introductionmentioning
confidence: 99%